2009
DOI: 10.3329/jhpn.v27i5.3636
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Food-hygiene Practices at Home and Childhood Diarrhoea in Hanoi, Viet Nam

Abstract: A cross-sectional study was conducted to investigate the potential factors of food-hygiene practices of mothers on the prevalence of diarrhoea among their children. Mothers who had children aged 6 months-5 years were recruited in a hamlet in Viet Nam. The food-hygiene practices included hand-washing, method of washing utensils, separation of utensils for raw and cooked food, and the location where foods were prepared for cooking. A face-to-face interview was conducted, and data on 206 mothers were analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Such factors include food preparation practices and child feces disposal practices. For example, a cross-sectional study in Viet Nam showed that the risk of childhood diarrhea was significantly higher among children whose mothers prepared food for cooking somewhere other than the table, compared to children whose mothers prepared food on the table [ 33 ]. A cross-sectional study using the data of the 2013 Nigerian Demographic and Health Survey reported that the increased risk of childhood diarrhea was significantly associated with unsafe child feces disposal practices of caretakers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such factors include food preparation practices and child feces disposal practices. For example, a cross-sectional study in Viet Nam showed that the risk of childhood diarrhea was significantly higher among children whose mothers prepared food for cooking somewhere other than the table, compared to children whose mothers prepared food on the table [ 33 ]. A cross-sectional study using the data of the 2013 Nigerian Demographic and Health Survey reported that the increased risk of childhood diarrhea was significantly associated with unsafe child feces disposal practices of caretakers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may also have been that the choice of ‘other’ was made by respondents who do not store food. Poor food hygiene practices are regarded as major contributors to diarrhoea [ 44 ], and households should be encouraged to keep cooked or perishable food in a refrigerator or cool conditions where possible.…”
Section: Discussionmentioning
confidence: 99%
“…Foods that are stored under unfavorable conditions are given to infants without being heated or are inadequately reheated, resulting in an increased intake of pathogenic germs. Proper cooking and frequent hand washing with soap can reduce the load of pathogens [ 18 , 20 , 21 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%